"It Is True in More Senses Than One, That Slavery Rests upon Hell!" Embodiment, Experience, and Evil in African American Discussions of Slavery and Slaveholders - Blum, Edward J. (The journal of religion, 2017)
The article presents the exploits of American slave, Henry Box Brown, along with his experience of being a slave and his attacks on 19th century slavery in the U.S. Details related to his opinions on the reference to hell and demons, along with the literary works of 19th century African Americans are included.